Promising Mesenchymal Stem Cell Intervention for Relieving Cardiac Recovery against Cardiotoxic Injury Modeling with Doxorubicin: A Novel Therapeutic Approach - Ozgermen Deva Basak Boztok; Haydardedeoglu Ali Evren; Yavuz Orhan (Acta Veterinaria, 2025)
Doxorubicin (DOX), a commonly used anti-neoplastic agent, has been associated with significant cardiotoxic effects, which limit its clinical utility. Recent studies suggest that mesenchymal stem cells (MSCs) may offer therapeutic potential in mitigating DOX-induced cardiotoxicity through their regenerative properties. This study aimed to evaluate the cardioprotective effects of fetal kidney-derived mesenchymal stem cells (FKD-MSCs) in a DOX-induced cardiotoxicity rat model. Thirty male Sprague-Dawley rats were divided into three groups: control, sham, and treatment. DOX (10 mg/kg) was administered to the sham and treatment groups to induce cardiotoxicity. The treatment group received intraperitoneal FKD-MSCs (2 × 106) three times at weekly intervals post-DOX administration. Immunohistochemical analyses were conducted to assess cardiac recovery. The 5-bromo-2-deoxyuridine (BrdU) labeling technique was used to track FKD-MSC localization in the cardiac tissue. The immunohistochemical findings demonstrated a significant improvement in the treatment group compared to the sham group. The BrdU-labeled FKD-MSCs were predominantly localized in cardiac muscle tissues, indicating their successful homing and integration into damaged cardiac regions. The results of the study indicate that FKD-MSCs significantly attenuated DOX-induced cardiotoxicity in rats, suggesting their potential as a novel therapeutic approach for cardioprotection. Further studies are warranted to investigate their clinical applications in managing chemotherapy-induced cardiotoxicity.